An unusual cause of obstructive jaundice - Abbara, Aula (BMJ Publishing Group, 2009)
An 80-year-old Caucasian woman presented with a 3-week history of painless jaundice, pruritis, dark urine and weight loss. Blood analysis demonstrated an obstructive jaundice pattern. A CT scan demonstrated a gas-filled duodenal diverticulum arising from the second part of the duodenum. Once food material was cleared from the diverticulum endoscopically, there was clinical and biochemical improvement. This case demonstrates an unusual cause of obstructive jaundice that has seldom been reported in the literature; once impacted food material was removed from the diverticulum, there was radiological improvement of the patient’s condition.